Influence of the Independent Learning Curriculum in Islamic Education Subjects - Maulidia, Martarosa; Mahasri Shobahiya (Yayasan Letiges Konsultan Sosial, 2024)
The discussion in this research concerns the influence of the Independent Learning Curriculum on Islamic Religious Education subjects. This research aims to describe the implementation of an Independent Learning Curriculum in Islamic Religious Education subjects and the supporting and inhibiting factors for Islamic Religious Education teachers in implementing the independent curriculum at a Public High School. The research approach used is qualitative with a case study method. The instruments used to collect data in this research are observation and interviews. Researchers observed the environment of a Public High School and the condition of the classes that were implementing the Independent Learning Curriculum. The research subjects were Islamic Religious Education subject teachers who had used the Independent Learning Curriculum for two periods in their classes. The research results show that implementing the Independent Learning Curriculum at Public High School was quite successful, with many supporting factors from the school, such as teachers and staff having high enthusiasm for holding Independent Learning Curriculum Implementation training. Apart from that, the facilities in the form of Chromebooks provided by the government to Public High Schools are also no less critical in realising the success of the Independent Learning Curriculum implementation. However, it does not deny that public high schools face inhibiting factors, such as human resources (HR) among students, which are still low, as evidenced by the school report cards, which are still yellow.